2012
DOI: 10.1097/cji.0b013e31823731a4
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccine-site Microenvironment Induced by Injection of Incomplete Freund's Adjuvant, With or Without Melanoma Peptides

Abstract: Cancer vaccines have not been optimized. They depend on adjuvants to create an immunogenic microenvironment for antigen presentation. However, remarkably little is understood about cellular and molecular changes induced by these adjuvants in the vaccine microenvironment. We hypothesized that vaccination induces dendritic cell activation in the dermal vaccination microenvironment but that regulatory processes may also limit the effectiveness of repeated vaccination. We evaluated biopsies from immunization sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…After removing duplicate entries, 462 studies were evaluated for inclusion based on the title and/or abstract, after which 114 potentially relevant studies were included for full-text examination; the majority of excluded studies were reviews or animal studies and 6 studies were not reported in English. From the 114 studies, full-text was unavailable for one study 13 , 2 studies were duplicates published under different titles 14,15 , one study only described the study design 16 and 6 studies did not report safety, tolerability and/or toxicity results 7,[17][18][19][20][21] . These together with 11 case reports [22][23][24][25][26][27][28][29][30][31][32] and 2 letters to the editor were excluded 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicate entries, 462 studies were evaluated for inclusion based on the title and/or abstract, after which 114 potentially relevant studies were included for full-text examination; the majority of excluded studies were reviews or animal studies and 6 studies were not reported in English. From the 114 studies, full-text was unavailable for one study 13 , 2 studies were duplicates published under different titles 14,15 , one study only described the study design 16 and 6 studies did not report safety, tolerability and/or toxicity results 7,[17][18][19][20][21] . These together with 11 case reports [22][23][24][25][26][27][28][29][30][31][32] and 2 letters to the editor were excluded 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…For the Mel48 trial (NCT00705640), all patients received the same vaccine of 12MP plus tetanus helper peptide (MELITAC 12.1), but differed in whether the vaccine peptides were administered at one or two sites [26-27]. …”
Section: Methodsmentioning
confidence: 99%
“…The vaccine was well tolerated with manageable side effects and no CTCAE grade 3/4 toxicities. Only local reactions at the vaccine site were frequently induced (90% of patients) most likely due to Montanide (20) and imiquimod (21).…”
Section: Discussionmentioning
confidence: 99%